2008
DOI: 10.1073/pnas.0808941106
|View full text |Cite
|
Sign up to set email alerts
|

Functional comparison of RGS9 splice isoforms in a living cell

Abstract: Two isoforms of the GTPase-activating protein, regulator of G protein signaling 9 (RGS9), control such fundamental functions as vision and behavior. RGS9 -1 regulates phototransduction in rods and cones, and RGS9 -2 regulates dopamine and opioid signaling in the basal ganglia. To determine their functional differences in the same intact cell, we replaced RGS9 -1 with RGS9 -2 in mouse rods. Surprisingly, RGS9 -2 not only supported normal photoresponse recovery under moderate light conditions but also outperform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…5A,C), with levels ranging between 1.7 and 4.9-fold above the wild type RGS9-1 content. We noted, however, that measurements of protein content had unusual variability among mice of the same line, leading us to suggest that rods from ggR9AP mice exhibit mosaicism in their expression of the transgene, as occasionally observed in transgenic lines using this promoter (Lem et al, 1991) and encountered in one of our recent studies (Martemyanov et al, 2008). Staining of R9AP −/− ggR9AP retinal flatmounts for R9AP revealed that this was indeed the case, as patches of rhodopsin-positive outer segments without R9AP expression were easily identified (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…5A,C), with levels ranging between 1.7 and 4.9-fold above the wild type RGS9-1 content. We noted, however, that measurements of protein content had unusual variability among mice of the same line, leading us to suggest that rods from ggR9AP mice exhibit mosaicism in their expression of the transgene, as occasionally observed in transgenic lines using this promoter (Lem et al, 1991) and encountered in one of our recent studies (Martemyanov et al, 2008). Staining of R9AP −/− ggR9AP retinal flatmounts for R9AP revealed that this was indeed the case, as patches of rhodopsin-positive outer segments without R9AP expression were easily identified (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The second, longer ‘dominant time constant’ (of 600–800 ms) observed in electrophysiological measurements on mouse rods has been proposed to reflect the time constant of such decay of free G* in vivo , on the basis of experiments incorporating RGS9-2 into rods [42]. We concur with that interpretation, and note that it conforms with the biochemical finding that, in the presence of the RGS domain of RGS9 but in the absence of PDE γ , the rate of GTP hydrolysis by activated transducin is around 1 s −1 [43] (in contrast to the much slower rate for purified transducin α-subunits, of around 0.05 s −1 [44]).…”
Section: Discussionmentioning
confidence: 99%
“…45,47,48 A recent report showed that RGS9-2 can functionally substitute for RGS9-1 in photoreceptors and, in fact, appears to be a more efficient inhibitor of transducin than RGS9-1. 49 …”
Section: Structure Of Gβ5–r7 Complexes the Role Of Rgs Ggl Andmentioning
confidence: 99%